The merit payment for broadcasting rights of spanish football: should we prioritize the show (goals) or the league table position? - Pinilla, J.; Negrín, M. A.; González-Martel, C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
In recent years the consumption of football events through audiovisual media has transcend national borders to globalize. The economic sustainability of the football clubs increasingly depends on media diffusion and their capacity to remain as an attractive, competitive and socially relevant product. Currently, in many European football leagues, including the Spanish “La Liga”, the club’s final position within the league table has a direct impact on the next five years’ revenues from TV broadcasting as a result of the joint selling of football broadcasting rights. This is commonly known as merit payment. However, the league table position does not have to be related to the quality of the match or the level of entertainment offered by the football team in the field, and therefore with the commercial possibilities of their matches in countries where football is not yet conceived as a sport of entertainment.